1983
DOI: 10.1200/jco.1983.1.12.750
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of doxifluridine in advanced colorectal adenocarcinoma.

Abstract: Doxifluridine, a new fluoropyrimidine derivative, was tested in a cooperative phase II trial by the Swiss Group for Clinical Cancer Research in advanced measurable colorectal cancer. The drug was given in a five consecutive day schedule by a bolus intravenous injection at a dose of 4 g/m2 per day and repeated every three to four weeks. Of 42 eligible patients, 40 had no previous chemotherapy. Response was defined in 27 patients having received two or more courses of doxifluridine. Seven responses (26%) were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Our results are similar to the reported trials in the treatment of advanced colorectal carcinoma [8,9,13,15]. There is no advantage for response dependent on routes of administra tion, but the one hour infusion showed low toxicities in contrast to the bolus injection and 6-hours infusion.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results are similar to the reported trials in the treatment of advanced colorectal carcinoma [8,9,13,15]. There is no advantage for response dependent on routes of administra tion, but the one hour infusion showed low toxicities in contrast to the bolus injection and 6-hours infusion.…”
Section: Discussionsupporting
confidence: 80%
“…In several contributions [8,9,13,15] as well as in our own previous experiences [14] it was clearly outlined that 5'dFUR is active for treatment of colorectal carcinoma. However, the optimal dose and route of application is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiotoxic effects of 5-FU have been extensively reported [3,4,5,6,7,8,9]. More recently, cardiotoxicity has been reported with doxifluridine [10], tegafur [11] and the oral fluoropyrimidines capecitabine [12,13,14,15,16] and UFT [17,18,19], predominantly in patients with colorectal cancer. We report a case of cardiotoxicity during the first cycle of capecitabine treatment in a woman with metastatic breast cancer, followed by a review of the available literature and a discussion of the possible pathophysiology of this cardiotoxicity and its implications for practice.…”
Section: Introductionmentioning
confidence: 99%
“…x 5 days in good-or poor-risk patients, respectively, demonstrated that 5dFUR has def inite activity in a variety of tumors usually sensitive to fluoropyrimidines, such as carcinoma of the breast [20], colon-rectum [21 ], and of the head and neck district [22], Furthermore, some comparative trials with 5FU for 5 consecutive days were carried out in colorectal cancer [23,24], Also in these trials, the infusion time seemed to affect both type and severity of toxicity. Indeed, a higher occur rence of neurologic (48%) and cardiac toxicity (19%) as compared to the parent compound was reported when 5dFUR was administered as intravenous bolus [23], while these side effects affected 23 and 1% of patients, respec tively, when 5dFUR was given as 1-hour intravenous infusion [24], In advanced SCCHN, the combination of CDDP and continuous intravenous infusion 5FU, with or without the addition of L-FA, has demonstrated to be a very active treatment itself, for unresectable or recurrent disease [4][5][6][7][8].…”
mentioning
confidence: 99%